A Theological Review of the Practice of Abortion among Unmarried Women in India - Tanhidy, Jamin; Pasaribu, Ronal; Vishal, Praveen; Simon, Simon (Sekolah Tinggi Teologi Simpson Ungaran, 2024)
In 2022, the Supreme Court of India has legalized abortion for all women, regardless of marital status. Consequently, all women in India are free to terminate their pregnancy without having to face a legal case. This decision is a breakthrough for new laws in India, including the issue of upholding women's rights. Even so, the act of arbitrary abortion is contrary to morals and Bible teachings. This article aims to discuss the legalization of abortion carried out by the Indian government from a biblical theology perspective by using a literature review approach. The findings of this research indicate that legalizing abortion through legislation is contrary to the biblical principle of the right to life. The government must guard abortion cases not only from political and socio-economic roles but also from religious beliefs and provide good sex education and a healthy environment for its people to suppress unwanted abortions. The role of parents in educating children and the role of the church in maturing the faith of the younger generation can prevent free sex and unsafe abortion in India. The contribution of this research is related to abortion, the right to life of the fetus, women's rights, sex education for the younger generation, parenting and government law.